Mitochondrial adaptations to high intensity interval training in older females and males. Issue 1 (2nd January 2020) - Chrøis, Karoline Maise; Dohlmann, Tine Lovsø; Søgaard, Ditte; Hansen, Camilla Vestergaard; Dela, Flemming; Helge, Jørn Wulff; Larsen, Steen
Abstract: Introduction : High intensity interval training (HIIT) has shown to be as effective as moderate intensity endurance training to improve metabolic health. However, the current knowledge on the effect of HIIT in older individuals is limited and it is uncertain whether the adaptations are sex specific. The aim was to investigate effects of HIIT on mitochondrial respiratory capacity and mitochondrial content in older females and males. Methods : Twenty-two older sedentary males ( n = 11) and females ( n = 11) completed 6 weeks of supervised HIIT 3 days per week. The training consisted of 5 × 1 min cycling (124 ± 3% of max power output at session 2–6 and 135 ± 3% of max power output at session 7–20) interspersed by 1½ min recovery. Before the intervention and 72 h after last training session a muscle biopsy was obtained and mitochondrial respiratory capacity, citrate synthase activity and proteins involved in mitochondria metabolism were assessed. Furthermore, body composition and ⩒O2 max were measured. Results : ⩒O2 max increased and body fat percentage decreased after HIIT in both sexes ( p < 0.05). In addition, CS activity and protein content of MnSOD and complex I-V increased in both sexes. Coupled and uncoupled mitochondrial respiratory capacity increased only in males. Mitochondrial respiratory capacity normalised to CS activity (intrinsic mitochondrial respiratory capacity) did not change following HIIT. Conclusion : HIIT induces favourable adaptions in skeletal muscle in older subjects by increasing mitochondrial content, which may help to maintain muscle oxidative capacity and slow down the process of sarcopenia associated with ageing.